Agroforestry for climate-resilient landscapes - RECOFTC; International Council for Research in Agroforestry; AWG-SF (RECOFTC, World Agroforestry (ICRAF), ASEAN Working Group on Social Forestry (AWG-SF), 2020)
This training manual provides basic guidance for trainers to design and deliver training that will help individuals or organizations increase their knowledge, skills and experience in agroforestry development. In addition, the exercises contained in this manual are designed to help participants foster the understanding and basic skills necessary to support farmers in developing effective and efficient agroforestry practices.